2014
DOI: 10.1016/j.pec.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Parental report of receipt of adolescent preventive health counseling services from pediatric providers

Abstract: Objectives Little is known about prevention-focused counseling health providers deliver to parents of adolescents. This study compared parental report of discussions with their adolescents’ providers about a range of adolescent prevention topics. Methods Between June and November 2009, a questionnaire was provided to parents accompanying adolescents aged 11-18 on outpatient clinic visits. Parents indicated, anonymouslym which of 22 prevention topics they remembered discussing with their adolescent's provider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…[4, 5] SCP counseling was somewhat more prevalent among parents whose children had sun-reactive skin or who had a family history of skin cancer. Nevertheless, more than 2 out of 5 of these parents did not recall discussing any of the assessed topics with their child’s provider, indicating missed opportunities for counseling those at higher risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4, 5] SCP counseling was somewhat more prevalent among parents whose children had sun-reactive skin or who had a family history of skin cancer. Nevertheless, more than 2 out of 5 of these parents did not recall discussing any of the assessed topics with their child’s provider, indicating missed opportunities for counseling those at higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…[4, 5] However, few studies have examined SCP counseling, with existing research focusing primarily on studies with healthcare providers. [6, 7] Despite being key decision-makers about their children’s health, the experiences of parents are largely absent.…”
Section: Introductionmentioning
confidence: 99%
“…Hispanic teens although most likely to receive counseling in all six areas (13.9; White 9.8%, Black, 10.3%) were also least likely to spend time alone with their doctor (23.6%; White 42.8%, Black 38.9%). Those from low income families (<200 federal poverty level) were less likely compared to those from higher income (27.6% versus 47%) families to have spent time alone with their clinician at their most recent visit (Irwin et al, 2009 (Akers et al, 2014). The results revealed that overall parents reported discussion of all health prevention topics was low.…”
Section: Anticipatory Guidance and Preventive Counselingmentioning
confidence: 90%
“…The results revealed that overall parents reported discussion of all health prevention topics was low. Topics considered more sensitive, for example sexual orientation (16%), pregnancy (20%), condom use/safe sex (20%) were discussed least often in comparison to more general topics including nutrition (50%), exercise/sports (47%) and seat belt/helmet safety (40%) that were reported most often by parents (Akers et al, 2014).…”
Section: Anticipatory Guidance and Preventive Counselingmentioning
confidence: 99%
“…Religious guiding activities related to fostering piety towards God Almighty and fostering noble character in Islamicbased educational institutions was a model of preventive counseling (Akers et al, 2014). It was programmatic so that students can develop their potential of religious fitrah optimally, by internalizing Islam values that contains in the holy book of the Al-Qur'an and the sunnah of the Prophet Muhammad.…”
Section: Student Guidance Model In Senior High Schoolymentioning
confidence: 99%